OPTIMALISASI LABA DALAM PERENCANAAN PRODUKSI MENGGUNAKAN PEMROGRAMAN LINIER - Wulan, Elis Ratna; Rejeki, Yosi Sri (EKSPANSI, 2016)
Abstract: Linear programming is mathematical method to resolve problems of allocating limited resources to achieve destination like to maximize profits and minimize costs. One of the methods to resolve linear programming problems is simplex method maximum. This research takes into the production of Flat Panel Monitor of four sizes and will point more products that contribute the main function of profit. Methodology for the optimization of the profit of LCDs manufacturing company, the linear programming and sensitivity analysis methods were applied. The four constraints of the LCDs production planning are (1) acquire of line space for production, (2) the assembly of products, (3) quality control and assurance hours (4) and packaging of material. Results in all three scenarios that the total profit is optimum and increases from scenario 1 to scenario 3. The difference between the profit of scenario 1 and scenario 2 is $ 257625, and gap between scenario 2 and scenario 3 is $ 171750. It can be concluded that the three scenarios for the production of the LCDs present the varying consequence of the maximum profit for the company. However, the third scenario is the most optimal solution for the maximization of the objective function. Keywords: Linear Programming, Simplex Method, Production Planning, Profit Optimization